THE INFLUENCE OF ALCOHOL TYPE AND CONCENTRATION ON THE PHASE BEHAVIOR AND INTERFACIAL TENSION IN OIL-SURFACTANTCOSURFACTANT-BRINE MIXTURE SYSTEM - Hadi Purnomo; Nuraini Nuraini; Tjuwati Makmur (Testing Center for Oil and Gas LEMIGAS, 2004)
The number of mechanism is limited for reducing the entrapment of oil in the pore space of reservoir rock and for mobilizing that residual which remains entrapped, thereby improving the microscopic displacement efficiency of a petroleum recovery process. After primary recovery by flow powered by the energy stored in the compressed fluids of reservoir, and secondary recovery by injection-pump driven water flooding, residual oil is trapped by the capillary pressure developed by interfacial tension in curved menisci between oil and water in the pore space. Figure 1.1 illustrates the interplay of capillary and viscous forces in the water flooding process. Shown in the figure is water displacing oil. The important point is that residual oil is trapped in the pore space by interfacial tension. To improve micros- copic displacement efficiency is to reduce interfacial tension between oil and water. Surfactant is surface active agent chemical that has two types of properties; lypofob (like water) and hydrofobÂ (like oil). The value of interfacial tension between oil and water is high, when surfactant is dissolved into water and contacts with oil, so that surfactant is not only soluble in the water, but also it is soluble in the oil. By addition of surfactant into the water and contact with oil can result in interfacial tension between oil and water from high (more less 20 - 30 dyne/cm) to lower interfacial tension (10-2 dyne/cm). To change the lower interfacial tension to the lowest interfacial tension conditions (10-4dyne/cm), cosurfactant in oil-surfactant-brine mixture is used. Alcohols are widely used in micellar surfactant systems for enhanced petroleum recovery and are variously called cosurfactant or cosolvent. In general, alcohols modify the physico- chemical properties in ways that are important to the design of surfactant-based process for improving petroleum recovery. This research is focused on alcohol effects on oil-surfactant-brine phase behavior and interfacial tension of oil-surfactant-brine system.